Insomnia and incident depression: role of objective sleep duration and natural history. (27th February 2015) - Fernandez‐Mendoza, Julio; Shea, Sarah; Vgontzas, Alexandros N.; Calhoun, Susan L.; Liao, Duanping; Bixler, Edward O.
Summary Longitudinal studies that have examined the association of insomnia with incident depression using objective sleep measures are very limited. The aim of this study was to examine the predictive role of the severity of insomnia for incident depression in a general population sample using psychometric and polysomnographic data. From a random, general population sample of 1741 individuals of the Penn State Adult Cohort, 1137 adults without depression were followed up with a structured telephone interview after 7.5 years. All subjects completed a full medical evaluation, 1‐night polysomnogram and Multiphasic Minnesota Personality Inventory at baseline. The incidence of depression was 15%. Poor sleep (odds ratio = 1.5, P = 0.001) and insomnia (odds ratio = 1.9, P = 0.031) were significantly associated with incident depression. The odds of incident depression were highest (odds ratio = 2.2, P = 0.019) in insomnia with objective short sleep duration and independent of Multiphasic Minnesota Personality Inventory Ego Strength scores, an index of poor coping resources. The persistence of insomnia and worsening of poor sleep into insomnia significantly increased the odds of incident depression (odds ratios ranged from 1.8 to 6.3), whereas their full remission did not (odds ratio ranged from 1.2 to 1.8). Insomnia with short sleep duration is associated with incident depression independent of poor coping resources, whereas the association of insomnia with normal sleep duration with incident depression was mediated by poor coping resources. Persistence and worsening of poor sleep or insomnia, but not their full remission, are significant predictors of incident depression. These data suggest that there is a significant relationship between the severity of insomnia and incident depression.